Implementasi Kurikulum Kulliyatul Mu’allimin al-Islamiyah (KMI) di Pondok Pesantren Darusy Syahadah Boyolali dan Pondok Pesantren Ta’mirul Islam Sragen: Implementation of The Kulliyatul Mu’alimin Al-Islamiyah (KMI) Curriculum at Darusy Syahadah Islamic Boarding School Boyolali and Ta’mirul Islam Islamic Boarding School Sragen - Muhammad Shofhan Amrullah Al - Arif; Muh. Nur Rochim Maksum; Mohammad Zakki Azani (Prodi PAI, Fakultas Tarbiyah, UNIDA GONTORs Tarbiyah, Universitas Darussalam Gontor, 2024)
The implementation of the Kulliyatul Mu'alimin Al-Islamiyah (KMI) curriculum in Islamic boarding schools is crucial for the development of quality education in Indonesia. This study focuses on the implementation of the KMI curriculum at Darusy Syahadah Islamic Boarding School Boyolali and Ta’mirul Islam Islamic Boarding School Sragen. Utilizing a qualitative case study approach, data were gathered through interviews, observations, and document analysis. The findings reveal the comprehensive planning, execution, and evaluation of the curriculum. Despite facing challenges such as integration with graduation competency standards, excessive subject load, limited resources, and teacher constraints, the schools employ various strategies including curriculum adjustments, teacher training, and student support mechanisms to enhance implementation. The leadership role of school administrators, effective curriculum coordination, and continuous evaluation mechanisms play pivotal roles in addressing challenges and improving curriculum implementation. This study underscores the importance of adaptive strategies and collaborative efforts in ensuring the effectiveness of the KMI curriculum in Islamic boarding schools.